(untitled) (Revista Escenarios Sociojurídicos, 2022)
This research aims to study in depth how the consumer is protected in the area of electronic commerce, currently in Colombia it is going through the best time of electronic commerce due to the efficiency and economic, environmental and social privileges, the way of impact on the world for changing the way of doing business carried out by companies that implement it due to the innovation and organization that is generated, this is due to the rapid evolution of information and communication technologies. With e-commerce we refer to a new modality and the substantial leap of carrying out commercial and business activities using electronic media, this in order to optimize the internal and external management of their respective companies. Currently, to help the progress of companies, they must have mastery of information defining processes and innovating tools to implement in terms of quality, quantity and purely commercial techniques, also brings with it advantages and disadvantages for the consuming part what to the development of the current I will explain them in writing.